(1288) A method for local and global minimization of concave function under linear constraints طريقة للتقليل المحلي والعالمي للدالة المقعرة في ظل قيود خطية - Omar, Amani (The Institute Of National Planning., 2018)
Global optimization involves solving mathematical programming problems that may have distinct local optima. In this paper, I present a method for locating a global minimum (maximum) of a concave (convex) function subjected to linear inequalities.